STUDY OF CLINICAL EFFICACY OF ORIGINAL AND GENERIC DRUGS OF IVABRADINE IN PATIENTS WITH STABLE ANGINA (СOMPARATIVE STUDY) - S. V. Povetkin; Ju. V. Luneva (Столичная издательская компания, 2018)
Aim. To study the therapeutic efficacy and safety of generic drug of ivabradine in comparison with the original drug in patients with stable angina. Material and methods. Patients with stable angina of II-III functional class (n=20) were included into an open randomized pilot study with a crosssectional design. Inclusion criterion: heart rate >70 beats/min during the use of beta-blockers. The comorbid cardiac pathology was represented by arterial hypertension of 1-3 degrees and chronic heart failure of I-III functional class. Initially, all patients underwent a clinical examination. Patients were randomized into the Group 1 receiving the original (Coraxan®, Servier,Serdix,Russia) or Group 2 receiving generic (Raenom®,Gedeon Richter,Hungary) drug of ivabradine (in addition to ongoing therapy), 5 mg BID. During the following month, the patients were monitored weekly. If necessary, the doses of the studied drugs were adjusted to achieve the target values of clinical indicators. After 4 weeks of therapy, study drugs in groups were replaced in equivalent doses; patients were observed for another 4 weeks.Results. A statistically significant decrease in heart rate (from 82.5±6.63 to 66.3±6.18 beats/minute in Group 1 and from 83.0±6.18 to 67.6±5.97 beats/min in the 2nd group, p<0.01 for both) and in blood pressure level was found in groups during the first 4 weeks of follow-up. Besides, there was a reduction in a number of weekly anginal attacks (76.1%, p<0.01) and sublingual nitroglycerin tablets (78.0%, p<0.01) in Group 1 as well as in Group 2 (75.2%, p<0.01 and 76.7%, p<0.01), respectively. The average daily dose of ivabradine in patients of the first group was 10 mg, in patients of the second group - 11 mg (p>0.05). Comparison of changes in the studied parameters during the treatment did not reveal statistically significant differences between the groups. Replacement of drugs in each group after 4 weeks of therapy ensured the preservation of the achieved effect of treatment. No adverse events were recorded during the 8-week course of treatment in both groups.Conclusion. A pilot comparative study showed that the studied generic drug of ivabradine has a therapeutic effect comparable to the original drug, but studies with a larger number of patients are necessary.